The principle of exceptionality in Canada's, Brazil's and Costa Rica's juvenile pre-trial detention - Brant, Gabriela; Soares Dallemole, Deborah; Motta Costa, Ana Paula (Universidad Hemisferios, 2025)
This research analyzes the institute of socio-educational pre-trial detention (PTD) and its relationship with the guiding principles of the Brazilian Child and Adolescent Statute (ECA), in particular, the principle of exceptionality, which characterizes this measure with the nature of ultima ratio. The hypothesis raised was that, currently, there is an expansive application of the PTD beyond the legal possibilities caused by the imprecision of the legislation that governs the institute. In order to reach such an understanding, a comparative analysis was developed, whose object was the juvenile legislation of Canada and Costa Rica compared to Brazilian regulations, as these first two have a restrictive view of state power. It was observed, in the legislative field, that the Latin American legislation analyzed has a more principled nature ‒with the direct naming of such notions, but without directly including them in the material content of its norms‒, while Canada has a legislation which absorbed such precepts in its articles, increasing the requirements for the determination of PDT and restricting the space for discretionary action by judges. In conclusion, it was found that there is a maintenance of the guardianship logic in the Brazilian legislation with the understanding that incarceration solves the problems (often of a social nature) related to the commitment of criminal infractions. Therefore, it is understood that the way in which the principle of exceptionality was incorporated into Brazilian legislation allows for spaces of judicial discretion and application of the restriction of freedom prior to the sentence in a broader way.